The role of fatty acid binding proteins in pain signalling - Mat Harun, Noraihan; Bennett, Andrew J.; Chapman, Victoria (2015)
FABPs are small proteins capable of interacting with and delivering ligands to a variety of proteins and receptors within the cells. The type of ligand bound by the FABP and the target receptor will influence a whole host of processes. For example, PPAR lipid ligands known to be bound by FABPs can be anti-nociceptive in animal models of pain, while different lipid species shown to be proniociceptive when activate the TRPVI receptor. As yet no interaction between FABPs and pronociceptive channels has been described in the central nervous system, but we believe that depending upon the ligand bound, FABPs may either be trafficked to the nucleus and interact with PPARs or move to the cell membrane to activate TRPVI. The objectives of this study are to identify the sites and types of TRPV, PPARs and FABPs expression in dorsal root ganglia. Taqman real time qPCR and in situ hybridization is used to study the genes expression and identify the cell typespecificity for PPARs and FABPs; and their co-localization with TRPV1 in rat dorsal root ganglia. Rat PPAR α, β and ɣ were amplified and subcloned into the pBluescript SK- plasmid and is used as DNA template for the synthesis of RNA probes for the in situ hybridization. For the future studies, Calcium Imaging and Bimolecular fluorescence complementation (BiFC) assays will be done to determine the influence of FABPs and specific ligands upon TRPV1 channel activity; and the interaction profile between FABPs and PPARs or TRPV1 respectively.